Newly Discovered Notes of a Sermon by Hugh Latimer - McGovern, Jonathan ca. 20./21. Jh. (2020)
This article presents a transcript and brief analysis of sermon notes by a young lawyer from Derbyshire named Anthony Gell, who attended a sermon by Hugh Latimer in London during the reign of Edward VI. In this forgotten sermon, Latimer discussed the subjects of fasting and clerical education, and recommended the foundation of clerical colleges.